Exergy-based tool path evaluation method of material and energy flows to support the sustainable-oriented intelligent manufacturing. (February 2022) - Li, Lin; Guo, Chaozhong; Yan, Jihong; Zhao, Fu; Sutherland, John W
The environmental performance of machining processes is of extreme importance in the field of sustainable manufacturing. The development of an environmental impact assessment method is a crucial strategy to realize energy and material efficient manufacturing, yet few studies have addressed energy and material flows using a common perspective. In principle, to realize the minimum environmental impact, energy and material flows must be viewed using the same metric; this is required to avoid impact shifting from energy to material or vice versa. In this paper, an environmental evaluation method for milling tool path strategies is proposed to support intelligent manufacturing, which considers energy flow (electricity provided to the machine tool and air compressor) and material flows (associated with the cutting tool, workpiece, and cutting fluid) for a milling process. The proposed method provides a quantitative calculation to characterize the total exergy loss in terms of energy and material flows. It is envisioned that total exergy loss can support quantitative decisions related to electricity consumption, tool wear, metal chips recycling, and cutting fluid loss. To demonstrate the applicability of the method, a case study is considered in which a milling tool path is selected to minimize exergy loss. The proposed method will be integrated into an intelligent control system for evaluating the total exergy loss of a milling process, which can assist manufacturers to make reliable decisions to reduce the environmental impact during machining stage in the industry 4.0 era.